(Co)Relatos entre a prática de jogos eletrônicos e as práticas corporais da cultura corporal de movimento manifestadas na educação física escolar - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This study refers to the research (Co)Reports from the practice of electronic games and bodily practices of Corporal Culture Movement expressed in Physical Education, linked to the Interdisciplinary Master of Education, Language and Technology, State University of Goiás. Research draws an analogy between the current condition of electronic games and the body practices, through mythological allegory of Pandora's Box. The main objective of the study was to analyze the (co) relations between the practice of electronic games and bodily practices of Body Culture Movement students in 9th grade of elementary school, expressed in Physical Education in three schools in the public education network Rio Verde / GO. The decision to initiate an investigation in three schools signaled the need to develop a qualitative study, from which, some methodological referrals were made. The first was to refer students to answer questionnaires to identify those who had more involvement with the practice of electronic games. After the screening there were only 14 subjects. This group was observed during the game practice in Electronic Games Laboratory (SLAB), as well as during the lessons of Physical Education. Finally, participated in two focus group sessions, ways to confront the content of his speeches to the records made during observations. In addition to the data collection instruments used together students; teachers of Physical Education participated in a semi-structured interview, in which they could express their understanding of the subject matter of this investigation. The intersection of the information gathered, it was possible to establish three categories of analysis, namely: interaction, sportivization and playfulness, which supported the empirical representation of the research. The study showed that the students surveyed have an involvement with arcade near the major world indices; are highly participatory and interactive, but do not represent the students "more skilled" within the body practices disseminated through the "sport at school". Signaled that the lessons of Physical Education remain breeding of non-critical concepts as hegemonic pedagogical practices; and, finally, that the body practices are present in class, although are not conducted on the basis of critical assumptions Movement of Body Culture. Thus, I believe, provisionally, that electronic games influence gamers to steer clear of body practices, especially those carried out outside the school environment, however, this is not a reality that is ready and finished, since the teachers hold the "Hope" released from Pandora's Box imprisoned in their teaching practice, which gives them the power to (re) release new levels for this game. In this perspective, I believe that further incursions must be made in the quagmire of this study object.
Keywords: Jogos eletrônicos; Práticas corporais; Educação física escolar; Cultura corporal de movimento; Eletronic games; Body practices; School physical education; Body culture's movement; CIENCIAS HUMANAS::EDUCACAO